MIRROR TALKING STRATEGY TO ENHANCE SPEAKING SKILL OF ENGLISH DEPARTMENT STUDENTS OF TIMOR UNIVERSITY - Erlinda Sonya Pale; Imanuel Kamlasi (Universitas Islam Negeri Alauddin Makassar, 2021)
The hesitation of the students of the English Department of Timor University to deliver speeches triggered the researchers to figure out a suitable method to cope with the issue. This study was conducted to discover whether mirror talk could bring a positive impact on improving the students’ speaking skills particularly in delivering the speech. The method to be utilized for conducting this study was the qualitative method. The performances of the students before and after the implementation of mirror talking were recorded to discover the comparison of both. After delivering the speech, the students were interviewed to reveal the reasons for their inability to perform well. There were 18 students said that lack of time preparation was the main cause of their failure to perform well, 40 students were having a problem with their confidence to cause them had bad performances and 32 students mentioned that they were not interested in delivering speech. Data analysis indicated that the students’ ability in delivering the speech particularly in pronunciation and confidence got improved after the practice of mirror talking. It is recommended then that the practice of mirror talking could be executed for other audiences.